PENGEMBANGAN ALAT PERMAINAN EDUKATIF (APE) â€œKARTU BACA-NGAJI ASYIKâ€ SEBAGAI MEDIA BELAJAR BAGI ANAK USIA DINI DI TK AISYIYAH KECAMATAN SOKARAJA KABUPATEN BANYUMAS - Tutuk Ningsih (IAIN Purwokerto, 2016)
Abstract: Playing methods are important in achieving the child's learning objectives. Therefore, educators should guide the course of the game in order not to hamper the development of children in terms of cognitive, affective, and psychomotor. Children are also given a place and opportunity as possible to play. Tools educational games (APE) are needed as a learning medium that will help the implementation of the method of play. In this study, at the design stage are at least three things to do, namely the analysis of concepts or ideas, translating the results of analysis of the concept, and describes the initial design of the game